Significant limitations of a systematic review and meta‐analysis of interventions to promote skin self‐examination: reply from the authors. (1st September 2019) - Ersser, S.J.; Dyson, J.; Muinonen‐Martin, A.
Abstract: Linked articles : Coups. Br J Dermatol 2019; 181 :640–641 . Ersser et al . Br J Dermatol 2019; 180 :1339–1347 .